Pengaruh Rekrutmen dan Pengalaman Kerja terhadap Prestasi Kerja dengan Penepatan Kerja sebagai Variabel Intervening pada Dinas Perhubungan Kabupaten Solok - Rani Pertama Sari; Jhon Very; Chintya Ones Charli (Universitas 45 Surabaya, 2025)
This study aims to determine how much influence Recruitment, Work Experience has on Work Performance with Job Placement as an intervening variable at the Solok Regency Transportation Office. This study consists of two Independent variables, namely Recruitment and Work Experience and one dependent, namely Work Performance and Job Placement as an Intervening variable. The method of data collection through surveys and questionnaires distributed to 43 respondents. The analysis method used is Multiple Linear Regression and Hypothesis Testing, Data Processing in this study uses the SmartPLS 3 program. The results of this study indicate that the influence of recruitment has a positive and significant effect on job placement at the Solok Regency Transportation Office, Work Experience has a positive and significant effect on Job Placement at the Solok Regency Transportation Office, Recruitment has a positive and significant effect on Job Performance at the Solok Regency Transportation Office, Work Experience has a positive and significant effect on Job Performance at the Solok Regency Transportation Office, Job Placement has a positive and significant effect on Job Performance at the Solok Regency Transportation Office, Recruitment on work performance through Job Determination as an intervening variable has a positive and insignificant effect on the Solok Regency Transportation Office, the influence of Work Experience on Work Performance with Job Determination as an intervening variable has a positive and significant effect on the Solok Regency Transportation Office.